Development of cassava starch-avicel PH 101 for coprocess diluent of direct compression tablet - Yudi Wicaksono; Nailis Syifa' (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Cassava starch is tablet excipient with poor of both flowability and compressibility which can not be used as diluent of direct tablet compression. The purpose of this research was to develop co-process of cassava starch-Avicel PH 101 for diluent of direct compression tablet. To achieve this goal, the thing that has been done are : (1) isolation of cassava starch (2) co-processing of cassava starch-Avicel PH 101 (3) testing of mechanic-physic properties of co-process of cassava starch-Avicel PH 101 (4) evaluation of co-process of cassava starch-Avicel PH 101 as diluent of direct compression tablet. The results indicated that ratio cassava starch-Avicel PH 101 (60:40) provided co-process with the best of mechanical-physical and compression properties. The best of mechanical-physical properties were flowability about 6,70±0,28 g/dt and tapping index about 12,57±1,18.%. The best compression properties of cassava starch-Avicel PH 101 co-process were crushing strength about 4,97±0,23 kp and friability about 0,52±0,03.% with disintegration time and tablet uniformity fulfill with requirement of pharmacopoeia.Key words: cassava starch, Avicel PH 101, co-process, direct compression tablet